Security of industrial control systems and cyber-physical systems : second International Workshop, CyberICPS 2016, Heraklion, Crete, Greece, September 26-30, 2016, Revised selected papers /: second International Workshop, CyberICPS 2016, Heraklion, Crete, Greece, September 26-30, 2016, Revised selected papers. (2017) - Unknown
No abstract available